SISTEM MONITORING ENERGI DAN BIAYA KONSUMSI LISTRIK RUMAH TANGGA BERBASIS IOT - Fia Magfirah; Widhiantoro, Dandun (Politeknik Negeri Jakarta, 2024)
In Indonesia, household electricity consumption dominates at 91.47%, increasing living costs. To tackle this, an Internet of Things based system for monitoring energy and electricity expenditure has been developed, accessible through a mobile app. This employs the PZEM-004T sensor linked to an ESP32 to measure electric parameters such as voltage, current, power, energy, and consumption costs. Gathered data is shown on an LCD and sent to Firebase, syncing with the app for easy monitoring by users. The app also offers features to download data and calculate electricity costs for varying periods. Testing of the PZEM-004T sensor showed voltage and current measurement accuracies of 98.5% and 99.89%, respectively, indicating high precision with minimal error. Connected to home appliances, it recorded 0.474 kWh of energy use, costing Rp 640.85. The app displays measurements of five electrical parameters and allows users to download monthly data in Excel format and estimate daily, monthly, and yearly electricity expenses.